Giant circular dichroism of large-area extrinsic chiral metal nanocrecents - Yane Wang (Nature Portfolio, 2018)
Abstract In this work, we demonstrate the strong extrinsic chirality of the larger-area metal nanocrescents by experiments and simulations. Our results show that the metal nanocrescent exhibits giant and tunable circular dichroism (CD) effect, which is intensively dependent on the incident angle of light. We attribute the giant extrinsic chirality of the metal nanocrescent to the excitation efficiencies difference of localized surface plasmon resonance (LSPR) modes for two kinds of circularly polarized light at a non-zero incident angle. In experiment, the largest CD of 0.37 is obtained at the wavelength of 826 nm with the incident angle of 60°. Furthermore, the CD spectra can be tuned flexibly by changing the metal nanocrescent diameter. Benefitting from the simple, low-cost and mature fabrication process, the proposed large-area metal nanocrescents are propitious to application.